Designing a Modified Salam Contract Model for the Halal Industry: Insights from Delphi-ANP Analysis - Atika Rukminastiti Masrifah Masrifah; Sri Herianingrum Herianingrum; Abdul Ghafar Ismail Ismail (Islamic Economics Journal, 2026)
This study addresses a gap in the Islamic supply chain finance literature: while factoring and reverse factoring models for conventional supply chains are well documented, no prior study has designed a Sharia-compliant financing business model that addresses the cash-to-cash cycle problem specific to the halal value chain. This is the first study to combine the Delphi and Analytic Network Process (Delphi–ANP) methods to design and validate a modified salam contract model for this purpose, drawing on three respondent groups: Sharia banking practitioners, regulators, and suppliers/fintech practitioners across four rounds of focus group discussion and in-depth interviews. The results show that differentiation of the Islamic bank's business model was ranked as the most important objective (weight 0.221), ahead of halal value chain development (0.204) and MSME development (0.194), while value proposition emerged as the most influential model criterion (weight 0.217). Based on these findings, the study proposes a Fund Distribution Product Scheme that uses salam contracts, in which Islamic banks finance suppliers who hold an underlying contract with a standby buyer. Theoretically, this study contributes a validated ANP-based decision structure for Islamic supply chain financing that can be extended to other value chains facing cash-to-cash cycle constraints. Practically, it offers Islamic financial institutions (IFIs) a ranked, evidence-based set of priorities for target market, distribution channel, and value proposition for implementing salam-based financing in the halal value chain industry.